2021
DOI: 10.1038/s41598-021-91577-6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of S100B serum levels and clinical factors in youth patients with mood disorders

Abstract: Mood disorders have been discussed as being in relation to glial pathology. S100B is a calcium-binding protein, and a marker of glial dysfunctions. Although alterations in the S100B expression may play a role in various central nervous system diseases, there are no studies on the potential role of S100B in mood disorders in adolescents and young adults . In a prospective two-year follow-up study, peripheral levels of S100B were investigated in 79 adolescent/young adult patients (aged 14–24 years), diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Previous research in an animal model has shown that SSRIs may prevent psychosocial stress from reducing the number of astrocytes in the hippocampus 41 . This finding is consistent with observations that antidepressant medication can reduce levels of S100B in serum 18 , 42 . It is thus possible that the patients in the current study would have had higher levels of S100B if they had not been taking antidepressants.…”
Section: Discussionsupporting
confidence: 93%
“…Previous research in an animal model has shown that SSRIs may prevent psychosocial stress from reducing the number of astrocytes in the hippocampus 41 . This finding is consistent with observations that antidepressant medication can reduce levels of S100B in serum 18 , 42 . It is thus possible that the patients in the current study would have had higher levels of S100B if they had not been taking antidepressants.…”
Section: Discussionsupporting
confidence: 93%
“…seems to be involved in several clinical states like depression (Rajewska-Rager et al, 2021) or trauma (Falcone et al, 2015), what limits its specificity.…”
Section: Discussionmentioning
confidence: 99%
“…No. : DY248, DY3175, DY367, DY1820-05, respectively) DuoSet ELISA Development Kits (R&D System, Minneapolis, MN, USA) according to the manufacturer's instructions, with minor modifications, as described previously (Rajewska-Rager et al, 2021). The standard curve ranges were 1500-23.4 pg/ mL (BDNF), 5000-78.1 pg/mL (proBDNF), 3000-46.9 pg/mL (NGFR), 2000-31.2 pg/mL (S100B).…”
Section: Methodsmentioning
confidence: 99%
“…No. : DY248, DY3175, DY367, DY1820-05, respectively) DuoSet ELISA Development Kits (R&D System, Minneapolis, MN, USA) according to the manufacturer's instructions, with minor modi cations, as described previously (42). The standard curve ranges were 1500-23.4 pg/ml (BDNF), 5000-78.1 pg/ml (proBDNF), 3000-46.9 pg/ml (NGFR), 2000 − 31.2 pg/ml (S100B).…”
Section: Bdnf Probdnf P75 Ntr S100b Plasma Level Elisa Determinationmentioning
confidence: 99%
“…S100B was also indicated as potential suicide marker in CSF post-mortem studies(59). In children and adolescent population, S100B seems to be involved in several clinical states like depression(42) or trauma (60), what limits its speci city.4.2. Executive functioning and BDNF pathwayExcepting the potential biomarker value, BDNF pathway has been analyzed in relation to executive functioning.…”
mentioning
confidence: 99%